2003
DOI: 10.1074/jbc.m208560200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate and Platelet-derived Growth Factor (PDGF) Act via PDGFβ Receptor-Sphingosine 1-Phosphate Receptor Complexes in Airway Smooth Muscle Cells

Abstract: Platelet-derived growth factor (PDGF) and sphingosine 1-phosphate (S1P) act via PDGF␤ receptor-S1P 1 receptor complexes in airway smooth muscle cells to promote mitogenic signaling. Several lines of evidence support this conclusion. First, both receptors were co-immunoprecipitated from cell lysates with specific anti-S1P 1 antibodies, indicating that they form a complex. Second, treatment of airway smooth muscle cells with PDGF stimulated the phosphorylation of p42/p44 MAPK, and this phosphorylated p42/p44 MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
124
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(134 citation statements)
references
References 36 publications
8
124
2
Order By: Relevance
“…Nonetheless, it is clear that heterotrimeric G proteins mediate a subset of signals initiated by diverse non-heptahelical receptors, including the insulin, IGF-1, EGF, and platelet-derived growth factor receptor tyrosine kinases and single membrane-spanning receptors for C-type natriuretic peptide and zona pellucida glycoprotein, integrins, and T cell receptors (49). Apart from our results with the IGF-1 and IGF-2/M6P receptors (31), heterotrimeric G protein activation resulting from SK1-dependent transactivation of S1P receptors has been shown to account for pertussis toxin-sensitive signaling by plateletderived growth factor receptor (50,51). Based on this small but growing body of evidence, it is tempting to speculate that S1P receptor transactivation represents a common mechanism of signal convergence that permits structurally diverse non-GPCRs to access heterotrimeric G protein signaling pathways.…”
Section: Discussioncontrasting
confidence: 42%
“…Nonetheless, it is clear that heterotrimeric G proteins mediate a subset of signals initiated by diverse non-heptahelical receptors, including the insulin, IGF-1, EGF, and platelet-derived growth factor receptor tyrosine kinases and single membrane-spanning receptors for C-type natriuretic peptide and zona pellucida glycoprotein, integrins, and T cell receptors (49). Apart from our results with the IGF-1 and IGF-2/M6P receptors (31), heterotrimeric G protein activation resulting from SK1-dependent transactivation of S1P receptors has been shown to account for pertussis toxin-sensitive signaling by plateletderived growth factor receptor (50,51). Based on this small but growing body of evidence, it is tempting to speculate that S1P receptor transactivation represents a common mechanism of signal convergence that permits structurally diverse non-GPCRs to access heterotrimeric G protein signaling pathways.…”
Section: Discussioncontrasting
confidence: 42%
“…Indeed, similar interactions have also been suggested between GPCR and receptor tyrosine kinases, since there exists a transactivation of S1P 1 with the PDGF receptor (26,27,34,54). In these reports, it has been shown that cell migration toward PDGF is dependent on expression of S1P 1 , and moreover PDGF is capable of activating this S1P receptor.…”
Section: Figmentioning
confidence: 76%
“…S1P receptors are also known to cross-communicate with other GPCRs as well as other plasma membrane receptors, including receptor-tyrosine kinases (24 -26). For example, S1P and platelet-derived growth factor (PDGF) have been shown to act via PDGF-␤-and S1P 1 -receptor complexes in airway smooth muscle cells (27).…”
mentioning
confidence: 99%
“…Similar apparently conflicting data exist for the PDGF receptor. Although some evidence suggests that PDGF activates SK1 and causes S1P-dependent S1P receptor activation (36), other data suggest that crosstalk between PDGF and S1P receptors occurs in the context of a physical complex between the two receptors (37,54,55). Whichever model is ultimately correct, both incorporate the notion that a heptahelical S1P receptor functions as an intermediate in PDGF receptor-mediated G protein activation.…”
Section: Discussionmentioning
confidence: 99%
“…The second model advanced to explain heterotrimeric G protein-dependent signaling by non-GPCRs is that the receptors generate some signal that activates an endogenous GPCR, which in turn catalyzes G protein activation. For example, the platelet-derived growth factor (PDGF) receptor has been shown to activate sphingosine kinase (SK) and cause recruitment of ␤-arrestins to G protein-coupled sphingosine 1-phosphate (S1P) receptors (36,37). However the evidence that this might represent a general model of GPCR transactivation is presently limited.…”
mentioning
confidence: 99%